The perception of cooperative learning in teaching and learning in central Malaysia high school / Ahmad Fahim Zulkifli and Muhammad Fikri Arif Adnan - Zulkifli, Ahmad Fahim; Adnan, Muhammad Fikri Arif (Research Management Centre (RMC), 2021)
The purpose of this study was to investigate the current understanding and perception of cooperative learning in teaching and learning in Malaysia High School. This study emphasized on teachers' views on cooperative learning approach to support their students' teaching and learning in classroom. The study uses the qualitative approach involving 10 academic staff of a local high school located at Subang Jaya, Selangor by using semi structured interview method. The findings showed positive perceptions and interest towards the cooperative learning approach in teaching and learning in secondary schools. There were many advantages of cooperative learning in teaching and learning both for staff and students. Nonetheless, this study founded time constraints, nature of the subject, students' capabilities, monitoring student learning, and learning assessments to be the barriers which influence teachers' disengagement with this student-centered approach. To summarize, data from this study warranted the authors to recommend educator to shift their teaching and learning from teacher-centered toward student-centered approach. Educators should also adopt the cooperative learning approach in classroom as it may help students to better link between the concepts and real world. Therefore, educators should invest considerable time to learn and practice this concept and plan their teaching and learning around their learners.